Interrelations between changes in parameters of HRV, EEG and cellular immunity at patients with chronic pyelonephrite and cholecystite - Popovych, Igor L; Kul’chyns’kyi, Andriy B; Korolyshyn, Tetyana A; Zukow, Walery (Journal of Education, Health and Sport, 2017)
Background. Previously we have shown within the immunological homunculus conception that take place causal relationships between induced by balneotherapy changes in parameters of EEG and HRV, on the one hand, and the parameters of humoral immunity, on the other hand. The purpose of this study is to find out the relationships between induced by balneotherapy changes in parameters of EEG and HRV, on the one hand, and the parameters of cellular immunity, on the other hand. Methods. In basal conditions in 33 men and 10 women with chronic pyelonephritis and cholecystitis in remission, we recorded twice, before and after balneotherapy at the spa Truskavets’, EEG (“NeuroCom Standard”) and HRV (“Cardiolab+VSR”). In blood estimated routine parameters of cellular immunity. Results. We detected that changes in relative level CD4+ T helper lymphocytes upregulated by parasympathetic outflows and β-rhythm generating structures that are projected onto the loci T3, T4 and P4, while downregulated by sympathetic outflows and β-rhythm generating structures that are projected onto the locus F7 as well as α-rhythm generating structures onto T6 and P4 loci. Level of CD8+ T cytolytic lymphocytes vice versa downregulated by parasympathetic outflows as well as δ-rhythm generating structures onto locus F7 and θ-rhythm generating structures onto the locus T3, while upregulated by θ-rhythm generating structures onto the locus T4. Level of CD16+ natural killers upregulated by sympathetic outflows and β-rhythm generating structures that are projected onto the loci T4, T5 and C3 as well as α-rhythm generating structures onto the locus T4, while downregulated by parasympathetic outflows and β-rhythm generating structures that are projected onto the loci Fp1 and F4 as well as α-rhythm generating structures onto the loci P4, O1 and O2, θ-rhythm generating structures onto the loci F7, T5, T6 and O2 as well as δ-rhythm generating structures that are projected onto the loci F7, T5 and T6. Level of 0-lymphocytes upregulated by sympathetic outflows and δ-rhythm generating structures that are projected onto the loci F7 and T5 as well as α-rhythm generating structures onto the loci P4 and O2, while downregulated by β-rhythm generating structures that are projected onto the loci T5 and O1. Conclusion. The results are supplemented and refined Tracey’s immunological homunculus conception.